2016
DOI: 10.18632/oncotarget.12151
|View full text |Cite
|
Sign up to set email alerts
|

BMP signaling and its paradoxical effects in tumorigenesis and dissemination

Abstract: Bone morphogenetic proteins (BMPs) play important roles in embryonic and postnatal development by regulating cell differentiation, proliferation, motility, and survival, thus maintaining homeostasis during organ and tissue development. BMPs can lead to tumorigenesis and regulate cancer progression in different stages. Therefore, we summarized studies on BMP expression, the clinical significance of BMP dysfunction in various cancer types, and the molecular regulation of various BMP-related signaling pathways. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 142 publications
0
70
0
1
Order By: Relevance
“…To date, ~20 members of the BMP subgroup have been identified (13). Recently, more evidence demonstrated that BMPs participate in cancer development and progression, such as colon cancer (14). It has been reported that BMP-9 promoted a proliferative response and exerted a remarkable anti-apoptotic function in hepatocellular carcinoma (HCC)…”
Section: Introductionmentioning
confidence: 99%
“…To date, ~20 members of the BMP subgroup have been identified (13). Recently, more evidence demonstrated that BMPs participate in cancer development and progression, such as colon cancer (14). It has been reported that BMP-9 promoted a proliferative response and exerted a remarkable anti-apoptotic function in hepatocellular carcinoma (HCC)…”
Section: Introductionmentioning
confidence: 99%
“…An autogenous cancellous bone graft was used to augment healing in this high‐risk fracture. Bone grafts are osteoinductive, including stimulation of bone morphogenic proteins, which may play a role in tumorigenesis and regulation of cancer progression . The dog in this report also received pamidronate to limit bone resorption.…”
Section: Discussionmentioning
confidence: 92%
“…Molecular and functional analyses of sprouting angiogenesis have uncovered a link between neuronal guidance and tip cell sprouting . Similarly, anti‐ and proangiogenic functions have been ascribed to various proteins involved in bone homeostasis . Emerging avenues further include the diverse functions elicited by microRNAs and the role of EC metabolism in angiogenesis .…”
Section: Resultsmentioning
confidence: 99%
“…BMPs belong to the TGF superfamily and consist of about 20 proteins that regulate multiple biological processes in development and morphogenesis . BMPs are synthesized in the cytoplasm as dimeric precursor proprotein complexes, which are cleaved by serine endoproteases before secretion …”
Section: Novel Angiogenic Regulators and Conceptsmentioning
confidence: 99%
See 1 more Smart Citation